Preparing Preservice English Language Teachers to Teach at Unprecedented Times: The Case of Turkey - Yastibas, Ahmet Erdost (JET (Journal of English Teaching), 2021)
COVID-19 has impacted education negatively to a certain extent by suspending schools and universities, ending face-to-face and practical education, and causing a rapid transition to distance education. These changes have led to several negative effects on teachers and students such as anxiety, stress, and depression, which demonstrates the importance of teacher preparedness to teach at unprecedented times such as COVID-19. Therefore, assessing and evaluating teacher preparedness has become significant. One way to do this is to evaluate teacher education programs with a new perspective developed considering the effects of COVID-19 on education. Therefore, the present study aimed to find out how teacher education programs can prepare teachers to teach at unprecedented times by focusing on the English language teacher education program (ELTEP) of Turkey. It was designed as a qualitative study in which the ELTEP of Turkey was used as the data collection tool. The collected data were content analyzed. The findings have shown that the ELTEP of Turkey can prepare preservice English language teachers to teach at unprecedented times through three psychological courses, five technology courses, and 21 pedagogical courses. The findings were discussed, and suggestions for further studies were made.